MiR-140 leads to MRE11 downregulation and ameliorates oxaliplatin treatment and therapy response in colorectal cancer patients - Horak, Josef; Dolnikova, Alexandra; Cumaogullari, Ozge; Cumova, Andrea; Navvabi, Nazila; Vodickova, Ludmila; Levy, Miroslav; Schneiderova, Michaela; Liska, Vaclav; Andera, Ladislav; Vodicka, Pavel; Opattova, Alena (Frontiers in Oncology, 2022)
Cancer therapy failure is an important challenge in cancer treatment. One of the most common reasons for therapy failure is the development of acquired resistance of cancer cells. DNA damaging agents are frequently used in the first-line chemotherapy regimens and DNA damage response and DNA repair pathways are significantly involved in the mechanisms of chemoresistance. MRE11, a part of the MRN complex, involved in double-strand breaks (DBSs) repair is connected to colorectal cancer (CRC) patients’ prognosis. Our previous results showed that single nucleotide polymorphisms (SNPs) in the 3’UTR miRNA binding sites of the MRE11 gene are associated with decreased cancer risk, but on the other hand, with shorter survival in CRC patients, which implies the role of microRNAs (miRNAs) regulation in CRC. The therapy of colorectal cancer utilizes oxaliplatin (oxalato(trans-l-1,2-diaminocyclohexane) platinum, which is often compromised with chemoresistance development. Therefore, there is a crucial clinical need for the understanding of cellular processes associated with drug resistance and improving the treatment response by applying efficient combination therapies. The main aim of this study was to investigate the effect of miRNAs on the oxaliplatin therapy response of CRC patients. By the in silico analysis, miR-140 was predicted to target MRE11 and modulate CRC prognosis. The lower expression of miR-140 was associated with the metastatic phenotype (p < 0.05) and poor progression-free survival (OR=0.4, p < 0.05). In the in vitro analysis, we used miRNA mimics to increase the level of miR-140 in the CRC cell line. This resulted in decreased proliferation of CRC cells (p<0.05). Increased level of miR-140 led also to increased sensitivity of cancer cells to oxaliplatin (p<0.05) and to the accumulation of DNA damage. Our results, both in vitro and in vivo, suggest that miR-140 may acts as a tumor suppressor and plays an important role in DBSs DNA repair and consequently CRC therapy response.